PENGARUH PENGADAAN SARANA AIR MINUM, PENYEDIAAN AKSES KREDIT, DAN PENATAAN PERMUKIMAN KUMUH TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT RENTAN PESISIR - Hamdan Hamdan (Universitas Islam Balitar, 2016)
This study aims to predict the impact of fresh water storage, credit access facility to cath fish, and restoration of slum housing toward low income community welfare in the coastal areas. This study used verificative-qualitative approach. This study took place in Tengkurak Village, Pontang District, Serang Regency, Banten. Sample of this study was 33 people and data were collected using questionnaire. The data were analyzed using regression analysis of single and triple predictors. The study revealed that there are significant effect of fresh water storage, credit access facility, and restiration of slum housing toward low income society welfare in the coastal areas in a single effect or altogether that contributes up to 68.3%.